Determination of Promotion and Brand Image on Purchasing Decisions through Trust - Yosepha, Sri Yanthy (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Abstract: The purpose of this literature research is expected to build hypotheses regarding the influence between variables which can later be used for further research in the scope of marketing management. The literature review research article on the determination of promotion and brand image on purchasing decisions through trust is a scientific literature article within the scope of marketing management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and is sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Promotion affects Trust; 2) Brand Image affects Trust; 3) Promotion affects Purchasing Decisions; 4) Brand Image affects Purchasing Decisions; 5) Trust affects Purchasing Decisions; 6) Promotion affects Purchasing Decisions through Trust; and 7) Brand Image affects Purchasing Decisions through Trust. Keywords: Trust, Purchase Decision, Promotion, Brand Image